The evaluation of village building program/thematic real work lecture (KKNT) MBKM's implementation at UIN Sunan Kalijaga - Muyassaroh, Muyassaroh; Sudiyatno, Sudiyatno; Putro, Nur Hidayanto Pancoro Setyo; Yunita, Rahma; Syafiqurrahman, Syafiqurrahman (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This study aims to determine the standards of MBKM Thematic KKN, how the implementation of this program at UIN Sunan Kalijaga, as well as to determine the gap between the existing standards and the form of implementation.  This evaluation research uses the descrepancy evaluation model with a descriptive qualitative approach. Data collection in this study used interview techniques, documentation, and was equipped with an open questionnaire. The data sources in this study at the interview stage were 7 resource persons 1 Head of PPM UIN Sunan Kalijaga, 2 Field Supervisor (DPL), 2 heads of Study Programs and 2 students, as well as 33 students as respondents on the open questionnaire instrument. The content validity of the open questionnaire in this study received a value of 0.958, this value was obtained with 5 experts. Observation and documentation are also important data source instruments. Evaluation results in this study are in accordance with existing standards, the village development policy/KKNT for MBKM at UIN Sunan Kalijaga is a derivative policy called KKN conversion. The purpose of this conversion KKN is in line with KKNT, but there are various policy details that are changed according to the situation and conditions of UIN Sunan Kalijaga. The recommendation from this research is that the village development policy/KKNT MBKM can be implemented well in universities but adjusted to the situation and circumstances in each university.